КУЛТУРАТА И ОБРАЗОВАНИЕТО ВО БИТОЛА И БИТОЛСКО КОН КРАЈОТ НА 1944 И ВО ПОЧЕТОКОТ НА 1945 ГОДИНА (Philological Studies, 2019)
After the liberation of Macedonia during the World War II on November 19, 1944, the government started to resolve the issues related to construction of the Macedonian State. An unavoidable part of these processes was also the solution of issues concerning the culture and the education. In the same direction, this paper emphasizes the culture and the education in Bitola and the Bitola area between late 1944 and in early 1945.
Keywords: Macedonia, Bitola, education, schools, pupils, culture